2005
DOI: 10.1158/1078-0432.ccr-05-0675
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cyclooxygenase-2 in Mediating the Effects of Histamine on Cell Proliferation and Vascular Endothelial Growth Factor Production in Colorectal Cancer

Abstract: Purpose: Activity of histidine decarboxylase, the key enzyme in the synthesis of histamine, has been shown to be increased in several types of human tumors.We attempted to establish whether the possible involvement of histidine decarboxylase and histamine in colorectal carcinogenesis might be mediated by the activation of the cyclooxygenase-2 (COX-2) pathway. Experimental Design: Expression/activity of histidine decarboxylase, histamine content, and prostaglandin E 2 (PGE 2 ) production were analyzed in 33 col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 45 publications
6
101
1
1
Order By: Relevance
“…2A). The specificity of these two antibodies was previously established by other methodologies elsewhere 37 and we confirmed it by the positive staining of infiltrating mast cells within breast specimen (data not shown).…”
Section: Resultssupporting
confidence: 87%
“…2A). The specificity of these two antibodies was previously established by other methodologies elsewhere 37 and we confirmed it by the positive staining of infiltrating mast cells within breast specimen (data not shown).…”
Section: Resultssupporting
confidence: 87%
“…Neuroprotection induced by hypoxic exposure is diminished by administration of the anti-VEGFR2/Flk1 blocking antibody or by the use of mutant mice lacking the hormone response element of the VEGF gene promoter in newborn mice (Laudenbach et al, 2007). Histamine enhances VEGF production in the granulation tissue and in cyclooxygenase-2-positive HT29 and Caco-2 cells through the H 2 receptor (Cianchi et al, 2005;Ghosh et al, 2001Ghosh et al, , 2002. We also found that endogenous histamine induced the expression of VEGF mRNA and protein in the cerebral cortex on exposure to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we quantified and analysed the kinetics of calcium accumulation in the mitochondrial compartment of HeLa and HCT116 cells in microtiter plates (Materials and methods). After stimulation of cells with A23 or an IP 3 -mobilizing agent (histamine (Hist) that only acts on HeLa, but not on HCT116 cells (Cianchi et al, 2005)), Ca 2 þ m increased rapidly within seconds. In contrast, treatment with an inhibitor of N-glycosylation (tunicamycin (TN)) (McDowell and Schwarz, 1988) or an inhibitor of SERCA pumps (thapsigargin (TG)) (Inesi and Sagara, 1992) (Figures 1c and d).…”
Section: Er Stress Induces Camentioning
confidence: 99%